The impact of climate change on rainwater harvesting in households in Poland - Joanna Gwoździej-Mazur; Piotr Jadwiszczak; Bartosz Kaźmierczak; Karina Kózka; Joanna Struk-Sokołowska; Katarzyna Wartalska; Marcin Wdowikowski (Applied Water Science, 2022)
Abstract In water management, climate changes require adaptation, protection of existing resources and the search for alternative water sources. Rainwater harvesting (RWH) is increasingly becoming an alternative water source, applicable for many directions of its use. The aim of the research was to analyse the influence of long-term climate change on the potential for rainwater harvesting in households in Central Europe in Poland. The analysis of long-term climate changes impact on the household rainwater harvesting potential was conducted for the 50-year period for 19 cities in Poland. The water balance model was operated in a day-step mode, and the research was carried out in four “time scales approach”. For the purpose of all analyses, a standard weekly water demand profile was developed. It includes the daily sub-profiles for every working day and weekend, covering the washing and toilet flushing needs for a 4-person household. In order to evaluate the long-term changes in residential harvesting in Poland, a hypothetical residential RWH was investigated in 19 locations and rainfall conditions. To illustrate the time-spatial variation of annual rainfall amounts in the analyzed period, the heat map was prepared as the pre-simulation stage. Results show that the design of RWH systems should be based on archival data and take into account the many years of rainfall changes. This will improve performance and secure benefits for the users of this system.